REQUIREMENTS FOR MEDIATORS IN FOREIGN COUNTRIES AND OTHER EXPERIENCES - Kodirov Murodillo Turgunboy ugli (Academia Science Repository, 2023)
This article will review the foreign experience of conducting mediation procedures in dispute resolution, analyze the requirements for mediators in foreign countries. It was noted that the introduction of mediation is a natural trend of today, a means of resolving conflicts in the family sphere, allowing the conflicting parties to get a more adequate result. It should be noted that in modern Uzbek legislation, the requirements for mediation and the mediator have received their legal consolidation, since in some cases it becomes obvious that this method of dispute resolution is in many ways superior to the traditional judicial process, since the advantages of mediation are numerous: this allows you to reduce the pressure on the judicial system and maintain partnerships between the parties, save time, finances, etc